THE INFLUENCE OF CUSTOMER TRUST AND CUSTOMER COMMITMENT ON CUSTOMER LOYALTY IN INDOMARET MEUNASAH BLANG KOTA JUANG DISTRICT - M Haikal Aulia; Deri Ulana; Lisa Elvina; Rizka Yani; Mulyadi (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
The research aims to determine the influence of customer trust and customer commitment on customer loyalty. The location of this research is Indomaret Meunasah Blang, Kota Juang District. This research uses a quantitative approach. The method used is a purposive sampling method. The number of samples used was 96 respondents. The data analysis method used is multiple regression. The research results show that the influence of customer trust on customer loyalty is obtained by a value of ????count5,692 >????????????????le1.985 with a significant value of 0.000 < 0.05. So it can be concluded that customer trust has a positive and significant effect on Indomaret customer loyalty. Customer commitment to customer loyalty obtained a value of ????count13,304 >???? t????????le1.985 with a significant value of 0.000 < 0.05. So it can be concluded that customer commitment has a positive and significant effect on Indomaret customer loyalty. Based on the simultaneous test, the variables Customer Trust and Customer Commitment together (simultaneously) have a significant influence on customer loyalty at Indomaret. This can be seen by the value ????count> ????????????????le obtained as 1433,394 > 3.09 with a significance of 0.000 < 0.05.